Carrying the idol for visarjan - Mumbai Archive Project Team (Jio Institute, 2024)
Bearers take turns carrying the idol of the Goddess as it passes through Versova Koliwada, stopping at households where aarti (waving the sacred fire in front of the deity) is performed.